Atypical choroideremia presenting with early‐onset macular atrophy. Issue 6 (28th January 2019) - Kontos, Georgios; Kwan, Jennifer; Xue, Kanmin; Patrício, Maria I.; Clouston, Penny; Packham, Emily; MacLaren, Robert E.; Downes, Susan M.
Abstract: Choroideremia is an X‐linked recessive retinal degeneration predominantly affecting hemizygous males. It is caused by mutations in the CHM gene that encodes the Rab escort protein‐1. Characteristic features include early nyctalopia followed by progressive constriction of peripheral visual fields and sparing of the central vision until late in life with a distinct fundoscopic appearance. We present the case of a 17‐year‐old male with a c.282delT in exon 4 of CHM that has not previously been reported. Phenotypically this patient presented with an atypical choroideremia phenotype of early central macular degeneration in addition to the classic peripheral fundus characteristic findings.